Deoxyribonucleic acid (DNA) splicing system from graph theoretic perspective - Mohd Ruslim, Nooradelena; Elizabeth, Marta; Yuhani, Yusof; Mohamad, Mohd Sham; Adzhar, Noraziah (IOP Publishing, 2021)
In 1987, Head introduced the recombinant process of deoxyribonucleic acid (DNA) splicing system through a framework of Formal Language Theory. To express this phenomenon, a comprehensive writing system of the rule sets, proper terms and definitions pioneerly introduced by Head. The analysis on the recombinant behavior of double-stranded DNA molecules, characteristics and various type of splicing systems has sparks the researcher to explore more splicing mechanism extensively. The aim of this paper is to give an exhaustive review on the application of graph in DNA splicing system.